Care in the home for seriously ill children with complex needs: A narrative literature review. (December 2015) - Ward, Cynthia; Glass, Nel; Ford, Rosemary
This article reviews contemporary literature on home care of the seriously ill child with complex care needs and the sick child/parent dyad. The literature search revealed three major themes, namely the increasing acuity of child illness, the evolving role of the parent as care provider, and the health professional as care provider. While there is much known about the complexity of care of children and the role of family in that care, little is known about what families require in terms of support and sustenance during the long years of care provision.